AI in Translation Education: Benefits and Risks: الذكاء الاصطناعي في تعليم الترجمة: الفوائد والمخاطر - El Hadj Said , Nabila (Maalim, 2026)
Artificial intelligence nowadays dominates various fields especially education. The integration of AI tools such as Google Translate, DeepL, and ChatGPT in the educational sector has revolutionized learning and teaching. AI has transformed traditional classes into digitally enhanced learning contexts through instant information access and interactive engaging learning experiences. However, there are some challenges and shortcomings in integrating AI in education in general and universities in particular. This study aims to explore the influence and challenges of AI tools in translation classes of Naama university. Findings reveal that these tools serve as significant resources in refining translation efficiency.